Analysis and Design of Standard Operating Procedures in the Revenue Cycle at PT RSE - Theharin S, Previa (Indonesian Journal Publisher, 2025)
PT RSE, which is the object of this research, is a company that sells electric vehicles, namely bicycles, motorbikes, and spare parts frames. PT RSE initially only sold electric bicycles, but the product received a positive response from the public. This positive response encouraged the company to start selling electric motors and spare parts frames in order to meet market needs that continue to change along with the times. The times have made PT RSE experience an increase in sales figures but the company has experienced several problems in the revenue cycle. These problems include the absence of recording stock of goods from sales return activities, there are duplicate tasks, credit limits are not checked, and improper purchase order documents are made. Based on these problems, the purpose of this study is to analyze and design revenue cycle Standard Operating Procedures (POS) to increase company effectiveness. The data collection methods in this research are interviews, observations, and documentation. These methods support the research results, namely designing a revenue cycle POS that can be used as a guideline to increase company effectiveness. POS design is carried out on sales procedures and cash receipts, sales and credit cash receipts, and sales return procedures at PT RSE. The POS that has been designed certainly needs to be evaluated regularly by PT RSE to create good internal control.